ANALISIS KESESUAIAN APB DES DENGAN PERENCANAAN PEMBANGUNAN DESA BERDASARKAN PP 43 TAHUN 2014 DI DESA KALIGADING KECAMATAN BOJA KABUPATEN KENDAL PROPINSI JAWA TENGAH - Widyartati, Penta; Indriastuti, Ariyani (Sekolah Tinggi Ilmu Ekonomi Semarang, 2019)
The Village Revenue and Expenditure Budget (APBDes) is the annual financial plan of the village government that is discussed and agreed upon jointly by the village government and Village Consultation, and is determined by village regulations. The mechanism for using village funds starts from the planning, implementation, accountability and utilization of village funds. In order for the use of village funds to be targeted and in accordance with the priorities of community needs, the planning process as a basis for implementing village funds is expected to be carried out in accordance with Government Regulation No. 43 of 2014 article 114 and article 117. From the results of the study obtained evidence that the Kaligading Village government has carried out the mandate in accordance with Government Regulation No. 43 of 2014 article 114 concerning deliberation for the screening of community aspirations which then results from the deliberations set forth in the RPJMDes.